(untitled) (Polifonia, 2015)
Neste trabalho, inscrito na análise de discurso francesa, analisaremos as representações de língua portuguesa de dois estudantes intercambistas no Brasil, a fim de problematizar os possíveis efeitos na subjetividade dessa via de experienciar a alteridade. Tradicionalmente, os movimentos migratórios são entendidos como investidas de mobilidade espacial entre países e regiões por um longo período de tempo. Portanto, trataremos as experiências de estudar em outro país como movimentos migratórios e problematizaremos os modos como se dá o encontro-confronto com uma outra língua, designada “estrangeira”, nesse contexto. PALAVRAS-CHAVE: representação, migração, aprendizagem de línguas MIGRATION, INTERNATIONAL MOBILITY, PORTUGUESE LANGUAGE REPRESENTATIONS: POSSIBLE EFFECTS ON INTERNATIONAL STUDENTS’ SUBJECTIVITY ABSTRACT: In this study, supported by the French discourse analysis, we aim to analyze the representations of the Portuguese Language of two foreign students in Brazil, in order to discuss the effects of subjectivity on the way they experience otherness. Traditionally, migratory movements are understood as attempts of spatial mobility between countries and regions over a long period of time. Therefore, we will treat the experiences of students on international mobility as migratory movements as well as discuss the contact and confrontation with another language, normally called “foreign”, in the context of exchange programs. KEYWORDS: representation, migration, language learning